2022
DOI: 10.1029/2021gl096225
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation Infrasound Interferometry on Mars

Abstract: A high‐sensitivity pressure sensor was deployed as part of the Mars Interior Exploration using Seismic Investigations, Geodesy and Heat Transport lander on Elysium Planitia in November 2018. We use pressure records from 1 October to 31 December 2019 (Sol 301–389) for frequencies between 0.1 and 0.5 Hz to infer relative sound‐speed changes in the Martian atmosphere using the autocorrelation infrasound interferometry method. We find that relative sound‐speed changes are up to ±15%, follow a similar pattern to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Future work will improve interior models, search for hidden seismic or infrasound events (Garcia et al 2021, Ortiz et al 2022, particularly with machine learning (Dahmen et al, 2022, Stott et al, 2022 and search for phases or long period signals not yet confirmed, including PKP phases (Irving et al 2022), surface wave overtones (Xu et al 2020), normal modes (Lognonné et al 2022) and tides (Pou et al 2021). As has been seen for the Apollo Lunar Surface Experiment (Bates et al 1979), we can expect decades of scientific analysis with SEIS and InSight data.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will improve interior models, search for hidden seismic or infrasound events (Garcia et al 2021, Ortiz et al 2022, particularly with machine learning (Dahmen et al, 2022, Stott et al, 2022 and search for phases or long period signals not yet confirmed, including PKP phases (Irving et al 2022), surface wave overtones (Xu et al 2020), normal modes (Lognonné et al 2022) and tides (Pou et al 2021). As has been seen for the Apollo Lunar Surface Experiment (Bates et al 1979), we can expect decades of scientific analysis with SEIS and InSight data.…”
Section: Discussionmentioning
confidence: 99%
“…Earthquakes, volcanic disturbances, chemical and nuclear explosions, and artificial energy sources such as vibration-producing trucks or even handheld hammer blows can provide seismic wavefields that can be modeled to determine the physical characteristics of the Earth over scales from meters to 10,000 km. Impulsive atmospheric sources such as explosions (e.g., Matoza et al, 2022), bolide sonic booms (D'Auria et al, 2006;Langston, 2004;Le Pichon, 2002), or even thunder (Lin and Langston, 2009a;Lin and Langston, 2009b), can be interesting in their own right as well as providing for new wavefields for investigating Earth structure using records from seismometers.…”
Section: A Brief Primer On Geophysical Sensing Modalitiesmentioning
confidence: 99%
“…While seismometers and infrasound sensors have been employed to measure signals from spacecraft re-entry events prior to the OSIRIS-REx sample return capsule (e.g., Edwards et al, 2007;ReVelle and Edwards, 2006), the OSIRIS-REx event is the first instance of DAS deployment to record a re-entry. Similarly, while DAS has not yet been deployed in extraterrestrial settings, data returned from seismometers and/or infrasound sensors have provided information about the seismic activity and structure of the Moon and Mars (e.g., Giardini et al, 2020;Nunn et al, 2020) and the atmosphere of Mars (e.g., Banfield et al, 2020;Ortiz et al, 2022).…”
Section: A Brief Primer On Geophysical Sensing Modalitiesmentioning
confidence: 99%